Taxonomic review of the expanded Plocama (Rubiaceae, Putorieae) from flora of Iran, with a new species and a new combination - Bordbar, Firouzeh; Mirtadzadini, Mansour (Phytotaxa, 2021)
Plocama ehrendorferi is described as a new species from southeast of Iran that can be easily distinguished from the related species P. bruguieri and P. kandaharensis by its compact leaves on the stem and shorter internodes, the bright green color of the plant, shorter and narrower leaf segments and the length of corolla. This study provides new information on the taxonomic state and geographical distribution of Plocama species from the flora of Iran. It is concluded that P. macrantha has been reported wrongly from Iran such that the reports of P. kandaharensis and P. olivieri cannot be confirmed.